ChemInform Abstract: Multicomponent versus Domino Reactions: One‐Pot Free‐Radical Synthesis of β‐Amino‐Ethers and β‐Amino‐Alcohols. Issue 19 (May 2015) - Rossi, Bianca; Pastori, Nadia; Prosperini, Simona; Punta, Carlo
Abstract: Quaternary β‐amino‐ethers and ‐alcohols are synthesized by optimized one‐pot, three‐component reaction of aryl amines, ketones, and ethers or alcohols mediated by a TiCl4 /Zn/tBuOOH system.